PROXY WARS IN THE ERA OF GLOBALIZATION IN THE PERSPECTIVE OF INTERNATIONAL LAW - I Putu Bagus Arya Krisna; I Wayan Novy Purwanto (Transpublika Publisher, 2023)
Along with the development of science and technology, there has also been a shift in the form of war which we know is synonymous with military force, firearms and artillery explosions. Marked by the emergence of Proxy War as a new style in the world of war. The absence of direct involvement and the existence of competition between the great powers between the parties is one of the characteristics of the Proxy War itself but the Proxy War itself still has an impact that is as dangerous as a normal war, because Proxies can be formed from within/outside the country which makes it be difficult to detect. This paper aims to find out how Proxy War exists in historical developments and to see and understand Proxy War in the present which is very closely related to cyber warfare. The method used was a normative legal research method whose research focuses on the relationship between norms and predicts their development in the future. The findings showed that proxy war as a new style of warfare creates its own worries. Because the close link between Proxy War and Cyber War can cause national instability in a country. If propaganda that occurs in cyberspace is spread widely and systematically, this has the potential to cause riots within a country.